The type material of spider wasps (Hymenoptera, Pompilidae) deposited in the Federal Scientific Center of the East Asia Terrestrial Biodiversity, Russian Academy of Sciences, Vladivostok, Russia - Loktionov, Valery M. (Zootaxa, 2022)
The type material of spider wasps deposited in the Federal Scientific Center of the East Asia Terrestrial Biodiversity, Far Eastern Branch of the Russian Academy of Sciences, Vladivostok, Russia is catalogued. In total, this includes 305 primary type specimens (31 holotypes and 274 paratypes) belonging to 62 species and 1 subspecies, described between 1962 and 2019 from Russia, Tajikistan, China, South Korea, Japan, Laos, Indonesia, and Sri Lanka. All 31 holotypes are illustrated with color photographs and black-and-white drawings. Photographs of the habitus, head, hypopygium and genitalia of three holotypes and photographs of the habitus and head of 23 holotypes are presented for the first time. References to the original description, type localities, current status, and distribution of taxa are given. Data on the labels of holotypes and paratypes with clarifications and English translations are provided.